The Arabic Language Learning System at the Center for Foreign Language Studies, Zainul Hasan Islamic University Genggong - Ainur Rofiq Sofa (Departement of Mathematics Education, 2024)
This article aims to discuss the Arabic language learning system at the Center for Foreign Language Studies (PSBA) of Zainul Hasan Islamic University (UNZAH) Genggong Probolinggo. Currently, there is a growing public interest in learning Arabic due to its significance in addressing various complex issues in the contemporary world. Numerous educational institutions are actively involved in the development and implementation of Arabic language education, both formally and informally. One such institution is Zainul Hasan Islamic University (UNZAH) Genggong Probolinggo, which has established the Center for Foreign Language Studies (PSBA) on its campus. This research is a qualitative field study utilizing a multidisciplinary approach, encompassing pedagogical, normative theological, juridical, sociological, and psychological aspects. The study results indicate that PSBA UNZAH Genggong offers courses in seven languages: English, Arabic, Chinese, Japanese, Korean, French, and German, for students who wish to deepen and develop their skills through an institution specifically established for the development of foreign languages, particularly Arabic. The learning system at PSBA UNZAH Genggong is a non-credit program managed by the Language Development Institute, aimed at students interested in advancing their Arabic language proficiency. PSBA UNZAH Genggong currently lacks a standardized curriculum, syllabus, or guidebook; its teaching materials are tentative and subject to change annually based on management policies. The learning model involves simultaneous classes held on the same day and time for each group, without any shifts in teaching hours or days by lecturers. This course program also does not confine learning strictly to the classroom. PSBA UNZAH Genggong has successfully enhanced the Arabic language skills of its students and produced competent Arabic language experts. The increase in achievements in Arabic language competitions, such as speeches, debates, and taqdimul qisshoh, at both district and national levels, demonstrates the improvement in students' Arabic language proficiency.